3rd workshop on Semantic Ambient Media Experience (SAME) - In conjunction with AmI-2010 - Lugmayr, Artur; Stockleben, B.; Kaario, J.; Pogorelc, B.; Risse, T. (2010)
The SAME workshop takes place for the 3rd time in 2010, and it's theme in this year was creating the business value-creation, vision, media theories and technology for ambient media. SAME differs from other workshops due to its interactive and creative touch and going beyond simple powerpoint presentations. Several results will be published by AMEA - the AMbient Media Association ( www.ambientmediaassociation.org ). © 2010 Springer-Verlag Berlin Heidelberg.